How Far the Humanistic User Experience in Workspace Collaboration Can Foster Self-Competence and Teamwork: Indonesian Organizational View - Grace Herlina Maria; Ozgen Eren; Iskandar Karto (E3S Web of Conferences)
This study investigates the influence of Humanistic User Experience (HUX) in Information and Communication Technology (ICT) workspaces on self-competence and teamwork within Indonesian organisations. Utilising a cross-sectional survey and the Partial Least Square Structural Equation Modeling (PLS-SEM), the research analyses responses from 305 employees in Greater Jakarta. The findings reveal that HUX significantly enhances self-competence, which, in turn, positively impacts teamwork. Self-competence is a critical mediator in the relationship between HUX and teamwork, highlighting the role of individual competencies in fostering collaborative outcomes. This study emphasises the importance of integrating humanistic principles in ICT design to create supportive work environments that enhance employee well-being and productivity. The implications suggest that organisations should adopt technologies that prioritise user-centred features to improve both individual competencies and teamwork. Future research should expand these findings across different cultural and organisational contexts to validate the results further.